2008
DOI: 10.1080/10715760802098859
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different vehicles to study the effect of tocopherols on gene expression in intestinal cells

Abstract: Recent studies have focused on the ability of tocopherols to regulate gene expression. For such experiments, the methodology used to deliver molecules to the cells is crucial and could lead to different results depending on the vehicle used. The objective of the present study was to compare commonly used tocopherol vehicles (ethanol, BSA and mixed micelles) in terms of toxicity, stabilization of tocopherols, uptake efficiency of tocopherols by cells and effect on gene expression. Lactate dehydrogenase measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 44 publications
(38 reference statements)
0
34
2
Order By: Relevance
“…For the delivery of tocopherol to cells, mixed micelles, which have similar lipid composition to those found in vivo [19], were prepared as previously described [13,20]. The concentration of tocopherols used in this study corresponds to the physiological concentration of tocopherols present in intestinal lumen [21].…”
Section: Preparation Of Tocopherol-rich Micellesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the delivery of tocopherol to cells, mixed micelles, which have similar lipid composition to those found in vivo [19], were prepared as previously described [13,20]. The concentration of tocopherols used in this study corresponds to the physiological concentration of tocopherols present in intestinal lumen [21].…”
Section: Preparation Of Tocopherol-rich Micellesmentioning
confidence: 99%
“…Experiments were performed as previously described [20]. The sequences of primers used for this study are reported in Supplementary Table 1.…”
Section: Rna Isolation and Qpcrmentioning
confidence: 99%
“…The cDNA was synthesized from 1 μg of total RNA using random primers and Moloney murine leukemia virus reverse transcriptase. Real-time quantitative polymerase chain reaction analyses were performed using the Mx3005P Real-Time PCR System (Stratagene, La Jolla, CA) as previously described [22]. The primers used were as follows: MTTP: 5′-CATTTCCTCATATTCAGCTTCTGTT-3′ and 5′-AGCTTGTACAGCCGGTCATT-3′; NPC1L1: 5′-GGCAGACCTCCCAAGTCGA-3′ and 5′-ATCCTTGAAGGTGAGCGGG-3′; SR-BI: 5′-CGGCTCGGAGAGCGACTAC-3′ and 5′-GGGCTTATTCTCCATCATCACC-3′; ATP binding cassette A1 (ABCA1): 5′-TCCAGGCCAG-TACGGAATTC-3′ and 5′-TTCCTCGCCAAACCAGTAGG-3′; and 18S, 5′-CGCCGCTAGAGGT-GAAATTCT-3′ and 5′-CATTCTTGGCAAATGCTTTCG-3′.…”
Section: Rna Isolation and Quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…The cDNA was synthesized from 1 μg of total RNA using random primers and Moloney murine leukemia virus reverse transcriptase. Real-time quantitative RT-PCR analyses were performed using the Mx3005P Real-Time PCR System (Stratagene, La Jolla, CA, USA) as previously described [27]. For each condition, expression was quantified in duplicate, and 18S mRNA was used as the endogenous control in the comparative cycle threshold (C T ) method [28].…”
Section: Rna Isolation and Qpcrmentioning
confidence: 99%